Nivolumab-Induced Thyroid Dysfunction - Lohit Kumbar; Chitra Selvan; Y P Ganavi (Wolters Kluwer Medknow Publications, 2021)
Nivolumab is one of human IgG4 monoclonal antibody belonging to the family of immune checkpoint inhibitors which acts by blocking ligand activation of programmed Cell death 1 receptor on T cells. Nivolumab has been approved for the management of patients with metastatic melanoma, metastatic squamous nonsmall cell lung carcinoma, renal cell carcinoma, and metastatic urothelial carcinoma. Associated side effects include increased risk of severe immune-mediated reactions involving the respiratory and gastrointestinal tracts, liver, kidney, and thyroid gland. Its effects on thyroid gland can result in hypothyroidism (7%), hyperthyroidism (1%), and thyroiditis (<1%), mostly developing around week 12 after the start of therapy with nivolumab. Here, we report a case of nivolumab-induced thyroid dysfunction